2009
DOI: 10.1016/j.ultras.2008.05.005
|View full text |Cite
|
Sign up to set email alerts
|

An improved automatic time-of-flight picker for medical ultrasound tomography

Abstract: Objective and motivation-Time-of-flight (TOF) tomography used by a clinical ultrasound tomography device can efficiently and reliably produce sound-speed images of the breast for cancer diagnosis. Accurate picking of TOFs of transmitted ultrasound signals is extremely important to ensure high-resolution and high-quality ultrasound sound-speed tomograms. Since manually picking is time-consuming for large datasets, we developed an improved automatic TOF picker based on the Akaike information criterion (AIC), as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 21 publications
(38 reference statements)
0
91
0
Order By: Relevance
“…The images are produced from algorithms that utilize "bent-ray" tomographic techniques for greater computational efficiency while accounting for refractive effects. 30,31 The exam is operator independent and, since the method is based on acquiring acoustic signals, there is no ionizing radiation.…”
Section: Iic Ust Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The images are produced from algorithms that utilize "bent-ray" tomographic techniques for greater computational efficiency while accounting for refractive effects. 30,31 The exam is operator independent and, since the method is based on acquiring acoustic signals, there is no ionizing radiation.…”
Section: Iic Ust Measurementsmentioning
confidence: 99%
“…Our previous studies have shown results consistent with this relationship. [29][30][31][32] This paper presents results from a study comparing the volume averaged sound speed (VASS) of the breast with mammographic percent density (MPD). The purpose of the study was to determine whether VASS is a viable measure of BD and a possible alternative to MPD.…”
Section: Introductionmentioning
confidence: 99%
“…Another important factor influencing the performance of our algorithm is signal-to-noise ratio of the acquired patient data. Although our in-house time-of-flight picker was tolerant to white noise, coherent noise in the ultrasound data might still affect the performance of the picker (Li et aL, 2009). Thus, low signal-to-noise of the data might affect the accuracy of our time-of-flight picks.…”
Section: Comparison Inmentioning
confidence: 99%
“…The time-of-flight was determined using an automated picker [18], and the speed of sound was computed from…”
Section: Signal Processingmentioning
confidence: 99%